AN ANALYSIS OF SLANG WORDS USED IN “THE HOLDOVERS” MOVIE SCRIPT - Ramadhani, Siti; Eliwarti, Eliwarti; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to find out the types and reasons for using slangwords by the characters in the “The Holdovers” movie script. The research design usedin this study is descriptive qualitative research with document analysis as the researchtype. The source of the data was taken from the script of “The Holdovers” moviewritten by David Hemingson. Allan and Burridge's (2006) theory was used to analyzethe data in this research. The finding shows that 96 data of slang words were found withFresh and Creative types as the most dominant type of slang words used by thecharacters in this movie, Then followed the Flippant type, Imitative type, Clipping type,and lastly the acronym type. Meanwhile, out of 192 frequencies of utterances, it wasfound that To Reveal Anger was the most frequently used reason for using slang wordsin “The Holdovers” movie script. It is followed by To Address, To Express Impression,To Humiliate, To Initiate Relax Conversation, To Form Intimate Atmosphere, and lastlyTo Show Intimacy.Key Words: Slang Words, Movie Script, The Holdovers